A Business Model Analysis On Hj Nina’s Rental Housing Using Business Model Canvas Approach - Puti Lenggo Ginny; Andy Andy (Primanomics : Jurnal Ekonomi & Bisnis, 2021)
Tangerang City has great potential for the growth of residential property projects. This region called thriving city due to economic growth which Tangerang City quite significantly from National. Terms of geographical, Tangerang City have access to strategic Jakarta so many transportation infrastructure could trigger growth property in the area. With the existence of business opportunities related to housing in Tangerang City, Mrs Hj Nina take advantage of these business opportunities by building land owned by property for a rented houses. But in running her business, Mrs Hj Nina has the main obstacle is competition around rented houses. One of the ways that Mrs Hj Nina’s rented house can explore the existing potential is by analyzing the right business model. Based on the results of the research on the identification of business model elements that exist in the house of Mrs Hj Nina, the author proposes several improvement programs for Mrs Hj Nina, namely expanding the house rent, develop business rented by diversifying business, adding facilities, doing community service, the owner having face to face meetings with rented houses, and house renters are active in the activities of local residents. With proposal the program for the improvement is expected to makes a business Mrs Hj Nina can develop and survived in the field of the business.